Impact of Unscrupulous Management on Moral Identity and Knowledge Sabotage Behavior - Alpison; Adi Rahmat; Adolf Bastian (Yayasan Education Al Aqsho Modern, 2022)
This study aims to investigate the impact of immoral management on moral identity and knowledge sabotage behavior. In particular, this study further aims to investigate and explain the impact of immoral management on knowledge sabotage behavior through moral identity in the workplace. In other words, this research is an explanatory research that uses quantitative methods to test hypotheses empirically. This study collects data by distributing questionnaires to employees who work as State Civil Apparatus (ASN) in several local government institutions in one of the provinces in Indonesia. The number of question items in this study were 31 question items consisting of: (1) 4 question items to measure the immoral management variable; (2) 5 item questions to measure the moral identity variable; and (3) 4 question items to measure the knowledge sabotage behavior variable. Thus, the number of samples of 288 has met the criteria for the minimum number of samples required in using SEM analysis. This study examines new mediating variables outside of the existing literature on the mechanisms underlying the process of the relationship between moralless management and knowledge sabotage behavior. In particular, this study investigates moral identity in the management function without morals. The findings clearly show that management without morals has a positive effect on moral identity. In addition, the results of this study also show that the influence of management without morals on knowledge sabotage behavior is fully mediated by moral identity. The results of the study also provide additional support regarding the importance of the function of non-moral management in organizations to shape positive attitudes and behaviors of employees.